PENGGUNAAN BAHASA JAWA DIALEK BANYUMAS DALAM SENI BEGALAN DI CILACAP - Retno Khoirul Mar’ah; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this study was (1) describe the layout variations sound/dialect pronunciation Banyumas in the begalan art at Cilacap, (2) describe the dialect lexical variation Banyumas in the begalan art at Cilacap, and (3) describe the grammatical variations of dialect Banyumas in the begalan art at Cilacap. This research was done in three stages, namely stages of data collection, data analysts, as well as exposure data analysis. Collection/provision carried out by methods refer to and capable, is a sequel technique refer to techniques involved free conversation and record. In this study the data from the oral form of the language used by the player dialog begalan art in the village of Jepara Kulon Binangun District of Cilacap in which there are words in the form of dialect Banyumas. Source of data derived from the use of the language spoken by the player begalan art. Information obtained in the form of dialogue sound used by players begalan art. After that, the data is classified and analyzed using the methods of unified referential. Afterwards, the data was analyzed qualitatively in terms of interpretation and inference. Results of this study are as follows. (1) Variation of the sound system / dialect pronunciation Banyumas contained in begalan in Cilacap art can be classified into two, namely vocal variety, ie the phoneme / i / is pronounced [i], the phoneme / u / pronounced [u], the phoneme / a / is pronounced [a] and the variation of the consonants, the phoneme / b / is pronounced [B], the phoneme / g / is pronounced [g], the phoneme / k / is pronounced [k], and the phoneme / w / is pronounced [w]. (2) Variation lexical dialect Banyumas in the art begalan in Cilacap variations lexical innovation, substitution, addition, and subtraction. (3) The variation of grammatical Banyumas dialect different from other dialects, including the standard dialect (Yogyakarta and Solo).Variasi Banyumas dialect grammatical form variations and variations affix reduplication.